2019
DOI: 10.1215/00127094-2018-0051
|View full text |Cite
|
Sign up to set email alerts
|

On the polynomial Szemerédi theorem in finite fields

Abstract: Let P 1 , . . . , P m ∈ Z[y] be any linearly independent polynomials with zero constant term. We show that there exists γ > 0 such that any subset of F q of size at least q 1−γ contains a nontrivial polynomial progression x, x + P 1 (y), . . . , x + P m (y), provided the characteristic of F q is large enough.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
71
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(73 citation statements)
references
References 20 publications
1
71
1
Order By: Relevance
“…The proof of Theorem 1.1 proceeds via a density increment argument where, as in [15], it is shown that any subset of [ ] with no nontrivial polynomial progressions has increased density on a long arithmetic progression with very small common difference. This is done by following the strategy for proving quantitative bounds in the polynomial Szemerédi theorem originating in [14], which is to first show that the count of polynomial progressions in a set is controlled by some Gowers -norm and then to show that, in certain situations, one can combine this -control with understanding of shorter progressions to deduce −1 -control. We refer to this second part of the argument as a 'degree-lowering' result, and it is here that it is crucial that 1 , .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The proof of Theorem 1.1 proceeds via a density increment argument where, as in [15], it is shown that any subset of [ ] with no nontrivial polynomial progressions has increased density on a long arithmetic progression with very small common difference. This is done by following the strategy for proving quantitative bounds in the polynomial Szemerédi theorem originating in [14], which is to first show that the count of polynomial progressions in a set is controlled by some Gowers -norm and then to show that, in certain situations, one can combine this -control with understanding of shorter progressions to deduce −1 -control. We refer to this second part of the argument as a 'degree-lowering' result, and it is here that it is crucial that 1 , .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the finite field situation of [14], the main challenge in this artice is to first prove that the count of polynomial progressions is controlled by some -norm. By using repeated applications of the van der Corput inequality following Bergelson and Leibman's [2] PET induction scheme, we can prove control in terms of an average of a certain family of Gowers box norms.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations